Exploration potential for copperbelt - style mineralisation in NW Province, Zambia; soil geochemistry as a targeting tool - Mwamba, John (Rhodes University, Faculty of Science, Department of Geology, 2018)
The NW Province of Zambia is fast becoming a major significant mining district challenging to usurp the economic importance of the traditional Copperbelt Province that has been mined for nearly a century. With latest developments at Kansanshi, Lumwana and Kalumbila mines exploration efforts in the search for Copperbelt style mineralisation have doubled up in the province in recent months. Traditional methods of stream sediment and soil sampling, geophysics, aerial photo and Landsat imagery interpretations have been employed in exploration targeting campaigns. This thesis asks the question: Can we use the Copperbelt geochemical footprint as a proxy to finding new copper deposits in NW Province? The challenge faced in such studies is that few geochemical datasets for old mines exist and the little that does is proprietary information. In some mines this dataset is entirely nonexistent - at least not in the public domain. Attempting to run orientation geochemical trials on such mines is not feasible at present due to maturity of mining and the levels of contamination of the natural environment that have occurred over several decades of mining. However, in tackling this question few Copperbelt geochemical datasets from Baluba, Nkana, Mimbula, Nchanga, Bwana Mkubwa, Mufulira West and Lufubu North were used. The findings presented in this report are that for Copperbelt style mineralisation Cu/Co, Cu/Ni, Cu/Ag ratios in soil geochemistry data should be in the ranges of 0.25 to 0.48 provided geochemical studies occurred in residual soils. These ratios hold true for sediment hosted copper-cobalt mineralisation hosted at various stratigraphic levels within the Roan Group or in upper levels elsewhere on the Central African Copperbelt. Geochemical dataset for the study areas presented in this report show that the soil geochemistry footprint in the province is not dissimilar to the soil geochemistry footprint of the traditional Copperbelt Province. This means there is great potential for finding Copperbelt style mineralisation in the province and other styles of mineralisation in which copper is associated with cobalt, lead, zinc, nickel, vanadium and molybdenum. The areas of study also possess requisite geological factors that are conducive to hosting Copperbelt style deposits. These factors include: favourable structural traps with similar trends to existing mines in the province, geophysical characteristics comparable to other deposits in the province, right geological package known to host multi-type deposits in the Katangan stratigraphic sequence, and similar geochemical footprints observed on other deposits within the Lufilian fold belt. For this reason, geochemical dataset must not be looked at in isolation but should be treated in considerations with other factors and geological environment.
Keywords: Mineralogy -- Zambia -- Copperbelt Province; River sediments -- Zambia -- Copperbelt Province; Soils -- Sampling -- Zambia -- Copperbelt Province; Prospecting -- Geophysical methods; Landsat satellites; Lufilian fold belt